1999
DOI: 10.1007/bf02874135
|View full text |Cite
|
Sign up to set email alerts
|

Myoglobin, creatine kinase MB, troponin T, and troponin I — rapid bedside assays in patients with acute chest pain

Abstract: Three new rapid, qualitative bedside immunoassays were evaluated in the diagnosis of patients with acute chest pain. The subjects, 122 patients in group 1 (bedside tests for myoglobin, creatine kinase MB) and 233 patients in group 2 (bedside tests for troponin I and sensitive troponin T) were admitted to hospital with acute chest pain for less than 12 h. The bedside tests were performed on admission, and 2, 4, and 6 h later. The correlation between the two parts of the rapid creatine kinase MB/myoglobin test d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…tion of cardiac troponin T might also be useful prognosticator in high risk patients whose standard evaluation of myocardial ischemia is not always accurate [3,4]. Several methods have been shown to be able to detect the troponin T such as enzymelinked immunosorbent assay (ELISA) [5], radioimmunoassay (RIA) [6] and immunochromatographic [7] tests. The first two are more usually used; however, they involve several steps and time consuming, whereas the second is a qualitative test.…”
Section: Introductionmentioning
confidence: 99%
“…tion of cardiac troponin T might also be useful prognosticator in high risk patients whose standard evaluation of myocardial ischemia is not always accurate [3,4]. Several methods have been shown to be able to detect the troponin T such as enzymelinked immunosorbent assay (ELISA) [5], radioimmunoassay (RIA) [6] and immunochromatographic [7] tests. The first two are more usually used; however, they involve several steps and time consuming, whereas the second is a qualitative test.…”
Section: Introductionmentioning
confidence: 99%
“…In the expected threshold value of these three markers (0.5 ng/mL for cTnI, 5 ng/mL for CKMB, and 50 ng/mL for Myo), visible bands appeared at the test lines, which indicated that the MICT performed well even without the MIR equipment. The LOD by naked eye was 0.5 ng/mL for cTnI, 5 ng/mL for CKMB, and 5 ng/mL for Myo 23.…”
Section: Resultsmentioning
confidence: 95%
“…The methods used for the diagnosis of AMI include conventional enzyme-linked immunosorbent assays (Wang et al, 2001), fluoroimmunoassays (Hayes et al, 2009), immunochromatographic tests (Penttil et al, 1999), spectrophotometric methods (Shiomi et al, 2005), electrochemiluminescence assays (Shen et al, 2011), and radioimmunoassays (Apple et al, 1997;Carraro et al, 1994). However, these approaches require multistep processing of samples, long diagnostic times, high costs, and trained personnel.…”
Section: Introductionmentioning
confidence: 98%